The experimental setup for high voltage breakdown studies in the high vacuum - Baturin, V.A.; Karpenko, O.Yu.; Profatilova, Ia.V.; Pustovoitov, S.O.; Miroshnichenko, V.I. (Вопросы атомной науки и техники, 2015)
An experimental setup for studying the processes occurring during breakdown in the high vacuum are described. The equipment is designed for comparative studies of pre-breakdown processes and the breakdown voltage of the different materials used for accelerator technology. Some first experimental results at this setup are shown in this paper. Описано експериментальне обладнання для вивчення процесів, які відбуваються при пробоях в умовах високого вакууму. Установка призначена для порівняльних досліджень передпробійних процесів та напруги пробою для різних матеріалів, що використовуються в прискорювальній техніці. Наведені перші експериментальні результати. Описана экспериментальная установка для изучения процессов, происходящих при пробое в условиях высокого вакуума. Установка предназначена для сравнительных исследований предпробойных процессов и напряжения пробоя для различных материалов, используемых в ускорительной технике. Приведены первые экспериментальные результаты.